1990
DOI: 10.1073/pnas.87.8.3112
|View full text |Cite
|
Sign up to set email alerts
|

NMR detection of creatine kinase expressed in liver of transgenic mice: determination of free ADP levels.

Abstract: To use the equilibrium established by creatine kinase (CK) to determine hepatic free ADP levels, the transcriptional control elements of the transthyretin gene were used to direct expression of the CK B isozyme to the livers of transgenic mice. Activities of CK ranging from 80-250 pmol per min per g (wet weight) were detected in liver extracts from five founder mice. The CK activity was stably transmitted to subsequent generations. Isozyme gels and immunoblots confirmed that the activity detected in extracts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 35 publications
6
92
0
Order By: Relevance
“…Donor hepatocytes were isolated from transgenic mice livers that express the brain isoform of the CK enzyme, CK-BB, under the control of liver-specific transthyretin promoter (CK-Tg), 14 using an in situ two-step collagenase perfusion procedure. 20,21 BDF mice were subjected to laparotomy, and 50 Gy of hepatic irradiation was delivered to anterior liver lobes by shielding the caudate lobe and other abdominal organs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Donor hepatocytes were isolated from transgenic mice livers that express the brain isoform of the CK enzyme, CK-BB, under the control of liver-specific transthyretin promoter (CK-Tg), 14 using an in situ two-step collagenase perfusion procedure. 20,21 BDF mice were subjected to laparotomy, and 50 Gy of hepatic irradiation was delivered to anterior liver lobes by shielding the caudate lobe and other abdominal organs.…”
Section: Methodsmentioning
confidence: 99%
“…13 Creatine kinase (CK) is an adenosine triphosphate (ATP)-buffering enzyme not normally expressed in the liver. 14 Koretsky et al 14 showed that CK expressed in hepatocytes of transgenic mice catalyzes the phosphorylation of creatine (Cr), generating phosphocreatine (PCr) that is absent in normal liver and generates a specific 31 P NMR spectra in vivo, which distinguishes the transgenic mouse liver from the livers of wild-type mice. Based on these findings, we hypothesized that ectopic expression of CK in donor hepatocytes could provide a specific marker enabling 31 P magnetic resonance spectroscopic imaging (MRSI) for assessment of hepatic repopulation by transplanted hepatocytes.…”
mentioning
confidence: 99%
“…5F). Thus, myoVI can effectively anchor the cargo in the presence of micromolar ADP concentrations that are physiological (19,(35)(36)(37), which implies that the differential effects of ADP on myoV and myoVI (see Fig. 5 A and B) could serve as an in vivo regulator that links myoVI function to the metabolic state of the cell (19).…”
Section: Myov and Myovi Coordinate Theirmentioning
confidence: 99%
“…Because only very few reports have focussed on mice (Ikeda and Tomonaga 1987;Spicer and Schulte 1992), a detailed in ventory of B-CK distribution in this animal is lacking. This is unfortunate because the mouse has recently prov en to be particularly useful for the examination of the bi ological role of the CK system, through the generation of animal models overexpressing (Koretsky et al 1990;Brosnan et al 1993), or lacking (van Deursen et al 1993, 1994a, 1994b) CK-isoenzymes. For these reasons we studied the reactivity of MoAb CK-BYK /21E10 in various mouse tissues.…”
Section: Discussionmentioning
confidence: 99%